Clinical impact of COVID-19 on people with substance use disorders. (26th October 2020) - Vallecillo, G; Perelló, R; Güerri, R; Fonseca, F; Torrens, M
Abstract: Background: People with substance use disorders are considered at increased risk of COVID-19 and its more serious complications, however data on the impact of COVID-19 are lacking. The study aimed to describe the clinical characteristics and outcomes of COVID-19 on people with substance use disorders. Methods: an observational study was carried out including patients aged ≥ years with COVID-19 pneumonia admitted to an urban hospital during March 12 to June 21, 2020. Results: Among 2078 patients admitted, 27 (1.3%) were people with substance use disorders: 23(85.2%) were men with a median age of 56.1 + 10.3 years and. The main SUD were alcohol in 18(66.7%) patients, heroine in 6(22.2%) and cocaine in 3(11.1%) and 24(88.8%) patients were on ongoing substance use disorder treatment. One or more comorbidities associated to COVID-19 risk were observed in 18(66.6%) of patients. During a median length of stay of 10 days (IQR:7-19), severe pneumonia developed in 7(25.9%) patients, acute respiratory distress syndrome in 5 (18.5%) and none died. Conclusion: Larger sample sizes and sero-epidemiological studies are needed to confirm the low incidence of severe COVID-19 on patients with SUD.